Water pollution: South Platte River - Nichols, Steven R., author; Skogerboe, Gaylord V., advisor; Ward, Robert C., committee member; Caulfield, Henry, committee member (Colorado State University. Libraries, 1972)
The Federal Government has been shown to be the primary initiator of state programs of water pollution control. The history of enabling legislation for water pollution control has implicitly established evidence as the backbone of pollution action. The Water Quality Act of 1965 required states to adopt criteria and plans of implementation and enforcement to then become standards for the state. However, a deficiency exists to require Federal approval of surveillance systems capable of providing data which could be applied to meet pollution control standards. Colorado responded to Federal requirements to establish a pollution control authority. Unfortunately, incorporated in the new law was the failure to devise an effective scheme whereby data collection could be applied to meet water quality objectives. An analysis of the data available for the South Platte River Basin in Colorado in general, and for the quality stations, Julesburg and Henderson in particular, showed inadequacies in the surveillance system. The inadequacies include the inability to accurately depict water quality trends and detect polluters. In addition, the data system proved to be inadequate for Colorado's objectives of protecting, maintaining and improving water quality. Furthermore, the need exists to re-evaluate and align the purposes of surveillance with the legal objectives of water pollution control. New collection techniques, including remote sensing and automatic monitoring in addition to the traditional grab sampling, may aid new programs in managing water pollution control.
Keywords: Water -- Pollution -- South Platte River (Colo. and Neb.)